2016
DOI: 10.1016/j.cattod.2015.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Nanosized TiO2—A promising catalyst for the aldol condensation of furfural with acetone in biomass upgrading

Abstract: a b s t r a c t Nanosized TiO 2 catalyst was successfully prepared by a simple green procedure and used in liquid phase aldol condensation of furfural with acetone, a key step in bio-fuel processing. In order to determine the effect of calcination temperature on catalytic properties of TiO 2 , the as-prepared TiO 2 and calcined TiO 2 (150-900• C) were studied by XRD, BET, TPD-CO 2 /NH 3 , TGA/DTG and FTIR evaluation. The catalytic performance of TiO 2 samples in aldol condensation of furfural with acetone was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 53 publications
2
35
1
Order By: Relevance
“…However, crude bio-oil from biomass [1][2][3] has some signicant disadvantages as vehicle fuel, such as high acid content, viscosity and corrosion, chemical instability and low caloric value. In order to solve these problems, catalytic cracking, 4,5 aldol condensation 6,7 and catalytic hydrodeoxygenation (HDO) have been adopted.…”
Section: Introductionmentioning
confidence: 99%
“…However, crude bio-oil from biomass [1][2][3] has some signicant disadvantages as vehicle fuel, such as high acid content, viscosity and corrosion, chemical instability and low caloric value. In order to solve these problems, catalytic cracking, 4,5 aldol condensation 6,7 and catalytic hydrodeoxygenation (HDO) have been adopted.…”
Section: Introductionmentioning
confidence: 99%
“…The best results were achieved with calcined catalyst sample having Mg/Al molar ratio equal to 3 at 100˚C (>95% furfural conversion and > 90% selectivity to the 4-(2-furyl)-3-buten-2-one and 1,5-di-2-furyl-2,4-pentadien-1-one). The catalytic performance of the prepared TiO 2 sample in aldol condensation of furfural with acetone was evaluated and compared with those for Mg-Al hydrotalcites [41] and BEA zeolite [42] (Scheme 6). It showed that uncalcined TiO 2 possesses good activity which could be competitive with that reported for other inorganic solids.…”
Section: Aldol Condensation Of Furfural With Acetonementioning
confidence: 99%
“…These condensation adducts are precursors for a large variety of renewable chemicals and, upon total hydrogenation, drop‐in diesel fuels. Aldol condensation involves the interaction between two molecules with carbonyl groups (aldehydes – furfural FFL or 5 – hydroximethylfurfural 5 – HMF – or ketones), acetone being the most studied linking molecule …”
Section: Introductionmentioning
confidence: 99%
“…Aldol condensation involves the interaction between two molecules with carbonyl groups (aldehydes -furfural FFL or 5 -hydroximethylfurfural 5 -HMF -or ketones), acetone being the most studied linking molecule. [5][6][7][8] There are several studies of the aldol condensation of acetone and furfural or 5-HMF using different homogeneous and heterogeneous catalysts, highlighting different hydroxides (NaOH and Ca(OH) 2 ) 9,10 and mixed oxides such as Mg-Zr or Mg-Al. 5,8 However, there are other bio-derived molecules with two -hydrogen positions that can alternatively be used for this purpose.…”
Section: Introductionmentioning
confidence: 99%